Software quality : Software and systems quality in distributed and mobile environments : 7th International Conference, SWQD 2015, Vienna, Austria, January 20-23, 2015, Proceedings /: Software and systems quality in distributed and mobile environments : 7th International Conference, SWQD 2015, Vienna, Austria, January 20-23, 2015, Proceedings. (2015) - Unknown
No abstract available